THE ROLE OF ORAL SPEECH IN LEARNING THE GERMAN LANGUAGE - Shakirova Gulbahor Alimovna (Galaxy International Interdisciplinary Research Journal, 2022)
Speaking is an oral form of verbal communication. When talking about the content of language teaching, it is necessary to identify three basic components:1) The linguistic component – is language and language material that provides students with the opportunity to enter into dialogue within the framework of topics and learning situations.2) The psychological component - mastering the skills and habits7 of expressive language. It is with the implementation of such.